Analysis of Human Resources Based on Interest and Talent in Cassava Processing Innovation through the 3P Program (Production, Packaging, Marketing) in Minggir Village - Lutfiya Yuni Rahmawati; Irma Soraya; Akhmad Jauharul Anshori; Indah Syaidatus Sa’diyah; Nanda Atiqoh Nurfani; Ahmad Fauzi Nurrohman (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This study aims to analyze human resources based on interests and talents in cassava processing innovation through the 3P Program (Production, Packaging, Marketing) in Minggir Village, highlighting its role in local economic development. Method: Using the ABCD (Asset-Based Community Development) approach, data were collected through interviews, participatory observation, and documentation to assess community involvement. Practical Application: The 3P Program encourages local women and cadres to engage in cassava product innovation, offering a replicable model for rural entrepreneurship and community empowerment. Conclusion: The research shows strong human resource potential in Minggir Village, evidenced by the active participation of PKK women and cadres in the 3P Program, contributing to sustainable local innovation and economic growth.